The relationship between depressive symptoms, metamemory, and prospective memory in older adults. Issue 1 (2nd January 2023) - Da Silva Coelho, Chloé; Zuber, Sascha; Künzi, Morgane; Joly-Burra, Emilie; Kliegel, Matthias
ABSTRACT: Introduction: Depression has been associated with impairments in different cognitive domains in younger adults, including prospective memory (PM; the ability to plan and execute intended actions in the future). However, it is still not well documented nor understood whether depression is also associated with impaired PM in older adults. The current study aimed to examine the association between depressive symptoms and PM in young-old and old-old adults, and to understand the potential influence of underlying factors, such as age, education, and metamemory representations (one's belief about their memory abilities). Method: Data of 394 older adults from the Vivre-Leben-Vivere study were included in the analyses ( Mage = 80.10 years, SD = 6.09; range = 70–98 years). Results: Bayesian ANCOVA revealed a 3-way interaction between depressive symptoms, age, and metamemory representations, indicating that the association between depressive symptoms and PM performance depended on age and metamemory representations. In the lower depressive symptoms group, old-old adults with higher metamemory representations performed as well as young-old adults independently of their metamemory representations. However, in the higher depressive symptoms group, old-old adults with higher metamemory representations performed more poorly than young-old adults with higher metamemory representations. Conclusion: This study indicates that metamemory representations may buffer the negative effect of age on PM performance only in old-old individuals with low depressive symptoms. Importantly, this result provides new insight into the mechanisms underlying the association between depressive symptoms and PM performance in older adults as well as into potential interventions.